Social Cohesion Indicators Bank: illustrative indicators to measure changes in social cohesion - Catholic Relief Services (Catholic Relief Services, 2019)
WHAT IS SOCIAL COHESION? Social cohesion is a concept with various interpretations.2 Some definitions emphasize social harmony and inclusion, human solidarity in diversity, and the inclusive wellbeing of a community or society. Others focus on the social fabric: the abundance of connections and associations in a society, and the presence of linkages and counterbalances that shape the relationship between citizen and the state. CRS views social cohesion as the strength, quality and diversity of relationships between and among individuals, groups and communities, coupled with linkages between society and the state, markets and other institutions, all based on trust, respect, mutuality and equal opportunity, for the dignity and wellbeing of every person and the common good of all.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; society / sociedade

Desafios para Moçambique - 2019 - Chichava, Sérgio (Instituto de Estudos Sociais e Económicos, 2019)
PARTE I – POLÍTICA O dever de pesquisar na periferia do mundo / Michel Cahen Multipartidarismo, geografia do voto e descentralização em Moçambique / Luís de Brito Desafios da descentralização fiscal em Moçambique: o caso dos municípios / Celeste Banze “Grão a grão enche a galinha o papo?” Evidências sobre o Imposto Pessoal Autárquico em 13 cidades moçambicanas / Eduardo Nguenha Identidades étnicas e governação municipal: algumas notas para a reflexão a partir do caso da Beira / Lúcio Posse PARTE II – ECONOMIA Dinâmicas de endividamento público em Moçambique na década 2009-2018: uma análise do contributo do livro Desafios para Moçambique / Yasfir Ibraimo Investimento, recursos naturais e Desafios para Moçambique / Carlos Muianga PARTE III – SOCIEDADE Protecção social nos livros Desafios para Moçambique : reflexão inspirada nos 12 anos de pesquisa do IESE / António Francisco Protecção social e poupança em 10 edições do Desafios: que tipo de protecção social pode Moçambique desenvolver? / Moisés Siúta Natureza demográfica e consequências do crescimento urbano em Moçambique / Rogers Hansine & Carlos Arnaldo PARTE IV – MOÇAMBIQUE NO MUNDO O IESE e a pesquisa sobre “Moçambique no Mundo” (2010-2018) / Sérgio Chichava Panorama, reflexões e desafios do IDE da China em Moçambique no contexto dos BRICS / Michael Sambo Brasil e Moçambique na cooperação Sul-Sul: entre avanços e recuos / Natália N. Fingermann Brasil e Moçambique: construindo a cooperação em defesa / Danilo Marcondes Na senda dos tractores: três crónicas para um retrato da cooperação Brasil-Moçambique / Lídia Cabral
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade